2012
DOI: 10.1111/j.1467-9450.2012.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems and post‐migration stress among multi‐traumatized refugees attending outpatient clinics upon resettlement to Norway

Abstract: Refugees have often been exposed to multiple traumas making them prone to mental health problems later. The aim of this study is to describe the prevalence and symptom load of psychiatric disorders in refugees admitted to psychiatric outpatient clinics and to investigate the relationship between multiple exposure to traumatic events, the severity of traumatic symptoms and post-migration stressors. A clinical sample of 61 refugee outpatients from psychiatric clinics in Southern Norway was cross-sectionally exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
130
3
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 123 publications
(179 reference statements)
6
130
3
9
Order By: Relevance
“…Even though the IES-R was not designed to make a categorical diagnosis of PTSD, it is common to quote cut-off scores in the literature. In this study, a relatively conservative cut-off sum score of 33 was applied, which is the recommended cut-off for probable post-traumatic stress symptoms severity levels in international (Creamer, Bell, & Failla, 2003) as well as in Norwegian samples of the general population (Heir, Piatigorsky, & Weisæth, 2009; Theodorescu, Hier, Hauff, Wentzel-Larsen, & Lien, 2012). The overall reliability for the IES-R was Cronbach’s α  = .95, with subscale Cronbach’s α values as follows: hyperarousal α  = .85, avoidance α  = .88, and intrusion α  = .91.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the IES-R was not designed to make a categorical diagnosis of PTSD, it is common to quote cut-off scores in the literature. In this study, a relatively conservative cut-off sum score of 33 was applied, which is the recommended cut-off for probable post-traumatic stress symptoms severity levels in international (Creamer, Bell, & Failla, 2003) as well as in Norwegian samples of the general population (Heir, Piatigorsky, & Weisæth, 2009; Theodorescu, Hier, Hauff, Wentzel-Larsen, & Lien, 2012). The overall reliability for the IES-R was Cronbach’s α  = .95, with subscale Cronbach’s α values as follows: hyperarousal α  = .85, avoidance α  = .88, and intrusion α  = .91.…”
Section: Methodsmentioning
confidence: 99%
“…The cut-off level for clinical caseness of general psychological distress was an SCL-90-R GSI total-score ≥ 65 (male: ≥ 0.74; female: ≥ 0.94) (Derogatis, 2009). Caseness for post-traumatic stress symptoms was an IES-R sum score ≥ 33 (Creamer et al, 2003; Heir et al, 2009; Theodorescu et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Each item assesses lifetime presence, and is then graded from 0 to 3 for current severity, over 2 signifying current presence. cPTSD requires all six symptom clusters to be present 15 . These calculations were carried out according to the SIDES authors' ''Trauma Assessment Packet & Software'' (van der Kolk & Smyth, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The manifestation of cPTSD in these more varied populations requires further description and exploration 10 . Two studies focused on conflict zone inhabitants in Kosova, Ethiopia, Gaza and Algeria 12,13 , one investigated Bosnian refugees 14 and, most recently, one investigated refugees living in Norway 15 . All these studies found much lower prevalences of cPTSD and its key symptoms compared to Western populations, thereby raising concerns as to the cross-cultural validity of the construct 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, these people are in danger of psychological disorders, especially depression and stress disorders after acute harms, due to numerous and prolong hardships they have experienced (Grritsen, et al, 2006). In extensive studies devoted to prevalence of depression among homeless fugitives, the prevalence rates varying from 9/8% to 67/4 % are reported (Teodorescu, et al, 2012). Kids are the most vulnerable fugitives to psychological agitation during the war, since they face the pressure of nativization with a totally unfamiliar environment, as well as, the stress and pressure of escaping from their own countries (Fazel, 2005).…”
Section: Introductionmentioning
confidence: 99%